Acute kidney injury in stable COPD and at exacerbation - Barakat MF (International Journal of COPD, 2015)
MF Barakat,1 HI McDonald,1 TJ Collier,1 L Smeeth,1 D Nitsch,1 JK Quint1,2 1Faculty of Epidemiology and Population Health, London School of Hygiene and Tropical Medicine, 2Department of Respiratory Epidemiology, Occupational Medicine and Public Health, National Heart and Lung Institute, Imperial College London, London, UK Background: While acute kidney injury (AKI) alone is associated with increased mortality, the incidence of hospital admission with AKI among stable and exacerbating COPD patients and the effect of concurrent AKI at COPD exacerbation on mortality is not known.Methods: A total of 189,561 individuals with COPD were identified from the Clinical Practice Research Datalink. Using Poisson and logistic regressions, we explored which factors predicted admission for AKI (identified in Hospital Episode Statistics) in this COPD cohort and concomitant AKI at a hospitalization for COPD exacerbation. Using survival analysis, we investigated the effect of concurrent AKI at exacerbation on mortality (n=36,107) and identified confounding factors.Results: The incidence of AKI in the total COPD cohort was 128/100,000 person-years. The prevalence of concomitant AKI at exacerbation was 1.9%, and the mortality rate in patients with AKI at exacerbation was 521/1,000 person-years. Male sex, older age, and lower glomerular filtration rate predicted higher risk of AKI or death. There was a 1.80 fold (95% confidence interval: 1.61, 2.03) increase in adjusted mortality within the first 6 months post COPD exacerbation in patients suffering from AKI and COPD exacerbation compared to those who were AKI free.Conclusion: In comparison to previous studies on general populations and hospitalizations, the incidence and prevalence of AKI is relatively high in COPD patients. Coexisting AKI at exacerbation is prognostic of poor outcome. Keywords: acute renal failure, mortality, emphysema, chronic bronchitis, prognosis